Proses Pembuatan Gaun Pesta Pagi Ready To Wear Bertema Cottagecore Dengan Variasi Lukis Kain Anggrek Hitam - Mien Zyahratil Umami; Maskhurun Ayufananie (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
Morning party dress is a dress worn in the morning and afternoon party occasions. Ready to wera dress are dress made with standard size. Thecottagecore themed ready to wear morning party dress prioritizes the choice of colors and shapes of the dress parts that give a simple impression of cottage life. This morning party dress uses fabric painting as decoration. The fabric painting motif used is a black orchid from Borneo forest. The purpose of making this final project is to find out the The process of making ready to wear themed cottagecore morning party dresses with black orchid fabric painting variation. The method used in this final project is observation method, library method and documentation. The result of this final project is a ready to wear themed cottagecore morning party dresses with black orchid fabric painting variation according to the design made by author. The process of making a ready to wear themed cottagecore morning party dresses with black orchid fabric painting variation is as follows: determining the design, preparing tools and materials, determinig the size, making the basic pattern, pattern drafting, cutting, painting, sewing and finishing.